A temporal record of microplastic pollution in Mediterranean seagrass soils. (15th March 2021) - Dahl, Martin; Bergman, Sanne; Björk, Mats; Diaz-Almela, Elena; Granberg, Maria; Gullström, Martin; Leiva-Dueñas, Carmen; Magnusson, Kerstin; Marco-Méndez, Candela; Piñeiro-Juncal, Nerea; Mateo, Miguel Ángel
Abstract: Plastic pollution is emerging as a potential threat to the marine environment. In the current study, we selected seagrass meadows, known to efficiently trap organic and inorganic particles, to investigate the concentrations and dynamics of microplastics in their soil. We assessed microplastic contamination and accumulation in 210 Pb dated soil cores collected in Posidonia oceanica meadows at three locations along the Spanish Mediterranean coast, with two sites located in the Almería region (Agua Amarga and Roquetas) and one at Cabrera Island (Santa Maria). Almería is known for its intense agricultural industry with 30 000 ha of plastic-covered greenhouses, while the Cabrera Island is situated far from urban areas. Microplastics were extracted using enzymatic digestion and density separation. The particles were characterized by visual identification and with Fourier-transformed infrared (FTIR) spectroscopy, and related to soil age-depth chronologies. Our findings showed that the microplastic contamination and accumulation was negligible until the mid-1970s, after which plastic particles increased dramatically, with the highest concentrations of microplastic particles (MPP) found in the recent (since 2012) surface soil of Agua Amarga (3819 MPP kg −1 ), followed by the top-most layers of the soil of the meadows in Roquetas (2173 kg −1 ) and Santa Maria (68–362 kg −1 ). The highest accumulation rate was seen in the Roquetas site (8832 MPP m −2 yr −1 ). The increase in microplastics in the seagrass soil was associated to land-use change following the intensification of the agricultural industry in the area, with a clear relationship between the development of the greenhouse industry in Almería and the concentration of microplastics in the historical soil record. This study shows a direct linkage between intense anthropogenic activity, an extensive use of plastics and high plastic contamination in coastal marine ecosystems such as seagrass meadows. We highlight the need of proper waste management to protect the coastal environment from continuous pollution. Graphical abstract: Image 1 Highlights: High microplastic accumulation was found close to intense agricultural areas. There was an exponential increase of microplastics in seagrass soils since the 1970s. There was a clear correlation between microplastic pollution and greenhouse production.